Job security among healthcare workers in Guangdong, China - He, Qingxia; Martins, Luís M. Dias; Wang, Shibin; Zhan, Qishan; Yu, Xiao; Ba, Zhiqiong; Li, Wangjiu; Huang, Huigen (Frontiers in Public Health, 2023)
Objective The objective of this study was to explore the sense of job security and its influencing factors among healthcare workers in Guangdong, China. Methods This cross-sectional study used stratified random sampling to enroll healthcare workers employed by hospitals across Guangdong province between September 2020 and October 2020. Results A total of 4,173 questionnaires were distributed, and 4,076 were returned for an effective recovery rate of 97.68%. The overall score for the sense of security was 64.85 ± 20.09, and the item means score was 2.95 ± 0.91. Multiple-linear regression analysis showed that work experience (years), education level, job position, specialty unit, employment type, marital status, job satisfaction, WPV frequency, daily sleep duration, weekly overtime hours, average monthly earnings (RMB), hospital level, and region were significantly associated with senses of poor security among healthcare workers (all P < 0.05). Conclusions Hospital workers in Guangdong reported relatively low levels of job security. Levels of job security were significantly associated with multiple factors which could be addressed by hospital practices to improve the sense of job security among healthcare workers.